Clínica Histórico-Cultural: caracterizando um método de atuação em psicoterapia - Clarindo, Janailson Monteiro (2020)
The Cultural-Historical Psychology, the main theoretical basis of this work, is classically linked to psychological fields related to School / Educational Psychology, Social Psychology and Work Psychology, while the clinical area and, more specifically, psychotherapy was relatively ignored by professionals and researchers who followed this approach. This research tries to contribute to fill this historical gap, focusing on the methodological field, starting from a question that we raised about how the theoretical bases and the method proposed by Vygotsky can serve as a foundation for psychotherapeutic practice. Based on this research question, the main objective of this thesis is to understand the articulation between the theoretical and methodological assumptions of Cultural-Historical Psychology and psychotherapeutic practice, aiming to characterize psychotherapeutic practice with a cultural-historical basis. For this, we conducted a qualitative research, in which a literature review was made, inspired by teh systematic review methodology, and the data produced was complemented by reflections from the analysis of clinic cultural-historical internship reports of Psychology students concluding their graduation and the analysis of three interviews with psychotherapists who use Cultural-Historical Psychology as the basis for their practices. Such data were also linked to our professional experience with the clinic, based on Vygotskian theory. The constructed data were worked from an interpretive analysis, inspired by the principles of Historical-Cultural Psychology. In this research, we take as theoretical analytical categories, specifically, the concepts of mediation, conscience and zone of proximal development (ZPD), the notion of subject in the cultural-historical psychotherapeutic clinic, psychopathology from the point of view of Cultural-Historical Psychology and experience. And the empirical analytical categories constructed were 1) the mediating techniques used in a clinical cultural-historical context and 2) the basic principles of a cultural-historical clinical performance. As main results, we saw that we still need research that deepens the theme of psychotherapeutic clinic from the cultural-historical point of view, but it is already possible to think of a psychotherapeutic clinical method from this perspective that is faithful to the theoretical-methodological principles of the theory. When this occurs, the main objective of a cultural-historical psychotherapist is to assume a mediating role in the dialogical interaction with a subject, aiming at the reframing of processes and the subsequent transformation of the action.